Evaluasi Penggunaan Kemasan PVC, PVDC, dan HDPE terhadap Stabilitas Fisik dan Kimia Produk Kapsul - Izdihar Putri, Salsabila Nur; gala , SELFINA (Journal of Research and Education Chemistry, 2026)
The physical and chemical stability of health supplement capsules is influenced by the packaging materials used, particularly their barrier capacity against moisture and oxygen. However, comparative studies on the effectiveness of PVC, PVDC, and HDPE packaging materials in maintaining capsule stability remain limited. This study evaluated the effects of PVC, PVDV, and HDPE packaging on the stability of L-glutathione capsules. The research was conducted using an experimental stability design under accelerated condition at 40°C ± 2°C and 75% ± 5% Relative Humidity, with time intervals of 10, 20, and 30 days. Stability testing followed product specifications, encompassing parameters such as appearance, weight variation, disintegration time, moisture content, and L-glutathione content (active ingredient). Results revealed that PVC packaged samples exhibited noncompliance in several parameters, including appearance, weight variation, and L-glutathione content. In contrast, PVDC and HDPE packaging maintained compliance across all tested parameters throughout the storage period. PVDC demonstrated the best performance in maintaining the highest L-glutathione content consistently across all observation intervals. Statistical analysis using two-way ANOVA with two replications revealed that packaging type, storage duration, and their interaction significantly influenced L-glutathione content (p < 0,05). These findings provide important implications for the pharmaceutical and supplement industries in determining optimal packaging materials, as well as for regulatory authorities in strengthening the evaluation of packaging suitability to ensure product quality, safety, and efficacy during storage.